Inflammation induced by increased frequency of intermittent hypoxia is attenuated by tempol administration - Zhang,J. (2015)
The levels of serum inflammatory cytokines and the activation of nuclear factor kappa B (NF-κB) and hypoxia inducible factor-1α (HIF-1α) in heart tissues in response to different frequencies of intermittent hypoxia (IH) and the antioxidant tempol were evaluated. Wistar rats (64 males, 200-220 g) were randomly divided into 6 experimental groups and 2 control groups. Four groups were exposed to IH 10, 20, 30, or 40 times/h. The other 2 experimental groups were challenged with IH (30 times/h) plus tempol, either beginning on day 0 (IH30T0) or on day 29 (IH30T29). After 6 weeks of challenge, serum levels of tumor necrosis factor (TNF)-α, intracellular adhesion molecule (ICAM)-1, and interleukin-10 were measured, and western blot analysis was used to detect NF-κB p65 and HIF-1α in myocardial tissues. Serum levels of TNF-α and ICAM-1 and myocardial expression of NF-κB p65 and HIF-1α were all significantly higher in IH rats than in controls (P<0.001). Increased IH frequency resulted in more significant changes. Administration of tempol in IH rats significantly reduced levels of TNF-α, ICAM-1, NF-κB and HIF-1α compared with the non-tempol-treated group (F=16.936, P<0.001). IH induced an inflammatory response in a frequency-dependent manner. Additionally, HIF-1α and NF-κB were increased following IH administration. Importantly, tempol treatment attenuated this effect.